Optimization of Microencapsulation Process of Green Coffee Extract With Spray Drying Method as a Dietary Supplement. - Claudia Gadizza Perdani; Tiara Ayu Prihardhini; Dodyk Pranowo (Indonesian Coffee and Cocoa Research Institute, 2020)
Green coffee has high content of chlorogenic acid which is potential to be developed into slimming diet supplement. Microencapsulation was used tomake herbal supplement. Spray drying process with the addition of maltodextrin as a coating material will protect the extract from high temperatures. The purpose of this study was to determine the percentage of maltodextrin and optimal skim milk to produce dietary supplement preparations and find out the quality of dietary supplement preparations obtained. Robusta coffee beans from Argopuro, Jember, East Java, was dry processed. This research optimized the microencapsulation process of green coffee extract using central composite design method. The method was response surface with two factors namely percentage of maltodextrin and percentage of skim milk. The response used was total phenolic content and antioxidant activity. The results showed the optimal percentage of maltodextrin and combined skim milk were 8.61% and 3.22% respectively with total phenol obtained at 58.75 mg GAE/g with an accuracy of 93.10% and IC50 65.10 ppm with an accuracy of 95.76%. Dietary supplement products on the market contain total phenol of 57.52 mg GAE/g and IC50 87.65 ppm. Comparison with other green coffee supplement products showed this microencapsulation have higher total phenol content and antioxidant activity.